Review. Issue 2 (1st August 2019) - Saeji, CedarBough T.
Pop City: Korean Popular Culture and the Selling of Place, Youjeong Oh (2018) Ithaca and London: Cornell University Press, 252 pp., ISBN 978-1-50173-071-9, h/bk, $42.95